Zooplankton composition of San Pedro Bay, Leyte, Philippines before and after weather disturbances from 2010 to 2015 - Bernabe, Darrienne Maureen P. (2016)
Zooplankton are considered the central diet of most pelagic animals which include commercially important fish. The seasonal disparity of the zooplankton structure is linked with hydrodynamic events and thus, are believed to be indicators of climate change. Monitoring and investigating the fluctuating abundance of zooplankton in relation to weather disturbances may be a key factor for fisheries management and climate change. Therefore, a study on the effect of weather disturbances such as typhoons is necessary. Sample collection was conducted once a month from three selected stations each with two depths. Qualitative and quantitative analyses were done in each station with the use of conical plankton net and a 2.2 L WILDCO alpha sampler, respectively. The possible effects of weather disturbances during the months of August 2013 and December 2014 were investigated using data from previous studies, dating back to 2010. In August 2013, during the Southwest monsoon and December 2014, after Typhoon Hagupit, an increase in total zooplankton with the highest values of 20,000 plus or minus 150 ind/L and 16,500 plus or minus 210 ind/L, respectively occurred. Similarly the dominant zooplankton group, the copepods, increased in August 2013 (5,000 plus or minus 760 ind/L) and in December 2014 (2,200 plus or minus 430 cells/L).